(untitled) (Fiep Bulletin - online, 2015)
Water losses during exercise are dependent on the intensity and the load of thermal stress. Water intake during physical activity has been recommended to replace the loss through perspiration and guarantee the homeostasis of the body. The performance of the athlete swimmer in the pool depends on various factors including genetics, training, motivation and diet. On the diet side there is an important factor that has received little attention from the swimmers and the trainers themselves: the quantity of water intake before, during and after training. The objective of this study was to measure the intake of liquids, the amount of perspiration, the level of dehydration and the coloration and specific gravity of urine during intensive swimming training sessions. Five male athletes with ages 20±1.8, height 188±5.55 cm and body mass 80.22±0.62 kg participated in this study during 30 days of the training. The total time to complete the training sessions was 165±12 minutes, the average temperature of the pool water was 28.83±1.45ºC and the ambient temperature 20.28±1.84ºC. The total amount of perspiration was 1.58±0.48L and the total intake of liquids was 553.14±109.52ml.h-1. The coloration of urine before training was 3.90±0.42 and after training was 2.58±0.85 with the specific gravity at 1.018,04±2.13 and 1.010,38±3.23, respectively. The variation in body masses was 0.07% after a hydric reposition of 8.27±51.62% above total water loss. In conclusion, it was established that swimming workouts in a pool did not mitigate a state of dehydration and the intake of liquids “ad líbitum” was sufficient to minimize the state of dehydration that was verified before the training began.